Docência Inovadora na Universidade - PINTO, Ivone Maciel (2011)
This thesis focuses on innovative teaching practices in university and they are associated to the categories derived from the concept of innovation built by the researcher, which will guide the construction process and analysis of data research such as: the ontological perspective, epistemological and methodological knowledge, intentionality, consciousness, autonomy, creativity, metacognition, transdisciplinarity,training, professional and educational practice. It is a paradigmatic trend which shows teacher training in the emancipatory perspective. The discussion is centered on complex thinking of the French thinker and philosopher Edgar Morin, and authors such as Capra, Prigogine and Maturana. Considering the complexitiy of the training process,the process of becoming professional and teaching practice, it seeks to base on a theoretical framework of the authors Alves and Oliveira; Anastasiou and Alves; Isaia and Bolzan; Cunha; Santos; Souza; Behrens; Lucarelli; Petraglia; Moraes; Moraes and Tower; Tower and Pujol; Magellan. The research takes place in the context of Pedagogy course, on the campus of Palmas Tocantins, with the participation of teachers that allowed this building and turned it into an unique experience. It is characterized as a qualitative study, whose method is the dialectical historical materialism and the goal designed is to analyze the teaching practices of teachers in pedagogy course at the University of Tocantins (UFT). The data indicate that pedagogical practices that are achieved in teaching at UFT do not characterize innovate pedagogical practices, according to the theoretical-methodological perspective that justifies this investigative work. The pedagogical practices developed by research teachers correspond to a kind of teaching situated in a conservative paradigm, do not comprehend and not know the foundations of emancipatory paradigm. The innovations that were evoked in practices that they realize do not set the necessary intention to break with the reproductivist logic and, consciously, to build a new relationship with the teaching, research and extension. These interpreted data call the attention and suggest studies at the university that lead to a reflection about emancipatory paradigm in order to contribute to ontological, epistemological and methodological referrals the knowledge.These are important to training and to provide a conscious and creative innovative teaching, in which the teacher can: a) reflect about his practice with new consciousness; b) use metacognitive knowledge, and c) intentionally build knowledge together to course academics, awakening them to emancipatory pedagogical practices.